The Risk Factors and Collateral System in Coronary Artery Disease among Patients in Bandung - Gabriella Graziani; Toni M. Aprami; R. B. Soeherman (Faculty of Medicine Universitas Padjadjaran, 2019)
Background: The slow blood flow may cause atherosclerotic plaque, leading to an obstruction in the arterial circulation, and thus resulting in among others myocardial ischemia. There are many risk factors associated with the collateral system such as dyslipidemia, obesity, hypertension, diabetes mellitus, and smoking habit. This study aimed to determine the association between risk factors and collateral system in patients in Bandung. Methods: This was an analytical cross-sectional study, using data of 186 medical records taken from Dr. Hasan Sadikin General Hospital in October 2013. The risk factors were assessed and the prevalence ratio reflected the association between the risk factors and the collateral system was analyzed.Results: The study revealed no significant association between each risk factor and the collateral system, including obesity (p=0.690), smoking (p=0.175), dyslipidemia (p=0.747), and diabetes mellitus (p=0.616); however, only hypertension was associated (p=0.020). Furthermore, no significant association was found between the number of risk factor and the collateral system (p=0.233).Conclusions: Of the risk factors published, only hypertension is a significant risk factor among patients in Bandung, while others including obesity, smoking, dyslipidemia and diabetes mellitus are not associated. Further study needs to be performed to explore other risk factors in coronary artery disease, and to prevent the disease among the population.